Two new species of Agaricus (Agaricaceae, Agaricales) from China - Dong, Rui-Xue; Tao, Si-Qi; Han, Xi-Xi; Zhao, Rui-Lin; Cao, Bin (Phytotaxa, 2025)
Two new species, Agaricus chuxiongensis and A. yangjiangensis, are described from China. Their macroscopic and microscopic features were carefully examined, and phylogenetic analyses based on ITS sequences were conducted. The molecular results provide strong support for recognizing these taxa as distinct members of A. sect. Agaricus. Detailed morphological descriptions and illustrations of both species are presented herein.